Structural, electrical and thermal studies of polyethylene based solid polymer electrolytes / Ri Hanum Yahaya Subban … [et al.] - Yahaya Subban, Ri Hanum; Tan, Winie; Ahmad, Azizah Hanom; Kamaruzaman, Norlida; Abdullah, Siti Zaubidah (2011)
Polymer based solid electrolytes are ionic conductors. As such the mechanism of ion transport through them depends on the type of polymer used as well as other components such as plasticisers or fillers. The transport mechanism in these materials can be quite complex. Different theoretical models could be employed to understand the conduction mechanism of polymer electrolyte. Rice and Roth model, quantum mechanical tunnelling (QMT) model, correlated barrier hopping (CBH) model and overlapping large polaron tunneling (OLPT) model. The Rice and Roth model is based on the hypothesis that in an ionic conductor there is an energy gap E above which conducting ions of mass M can be thermally excited from localized ionic states to free ion-loke states in which an ion propagates throughout the solid with a velocity v = (2E/M)1/2. From Rice and Roth model, the conductivity is given by σ= 2/3 [(Ze2)/kTM]ln Et exp (-E/kT), where x is the time to travel between two complexation sites,- e is the electronic charge n is the density of free ions, k is Boltzmann constant and T is the absolute temperature, t could be obtained by dividing the distance between the two complexation sites by the velocity of the ion obtained by equating the translational kinetic energy of the ion to the activation energy, Ea. Thus the number of free ions n can be calculated. The calculated values of n can then be used to calculate the ionic mobility p. using equation σ = nqµ. Thus the number the values of n and |i could be used to analyse quantitatively the conductivity behavior and transport mechanism of polymer electrolyte. On the other hand the QMT, CBH and OLPT models are used to interpret the temperature dependence conductivity behavior of polymer electrolytes.